PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN KECERDASAN EMOSIONAL GURU TERHADAP KINERJA GURU SMK NEGERI DI KOTA METRO LAMPUNG - Farid Pathurrahman; Juhri AM; Muhammad Ihsan Dacholfany (Pascasarjana IAIN Metro, 2020)
School Principal as the leader in particular school is influential to the teacher performance, in the effort of raising the performance in order to achieve the educational goal of the school. The leader has responsibility both physically and non-physically for the successful performance of the school. The principal's leadership must be able to influence all the school employees so that they are willing to work hard to improve performance voluntarily and passionately in achieving the vision, mission and goals of the school. Emotional Intelligence of the teacher will be able to send out warmth, awareness of one's own feelings, having sensitivity to the feelings of others and will be able to overcome emotional problems openly.This present study aims to: (1). know the contribution of principal’s leadership style toward the state vocational teachers’ performances in Metro City, Lampung, (2) know the contribution of the emotional intelligence of teachers to the performance of vocational state school teachers in Metro City, Lampung and (3) both the contribution of principal’s leadership style and emotional intelligence of the teachers toward the state vocational teachers’ in Metro City, Lampung.This research was descriptive study design used quantitative approach through regression analysis. This research aimed to know the influence between independent variable and dependent variable. The correlative study aimed to know whether there is any influence or not between two variables or more. The researcher decided 336 teachers as the population of the research and 77 teachers of 336 teachers as the sample of the research. The try out was 30 teachers of the rest of the research population which the sample has been previously determined.Due to theoretical assumption and the conclusions of data analysis, it can be concluded that: both the principal's leadership style (X1) and emotional intelligence (X2) have positive and significant contribution to the performance of teacher (Y) of State Vocational Schools in Metro City. This conclusion was supported by the analysis findings. There was positive and significant contribution of the principal's leadership style toward the teacher’s performance. The number of the contribution of the principal's leadership style to performance in this study was based on the results of calculations at the sufficient category. There was positive and significant contribution between emotional intelligence on teacher performance. The number of emotional intelligence contribution to teacher performance in this study was based on the results of calculations at the sufficient category and simultaneously there was a positive and significant contribution between the principal's leadership style and emotional intelligence on teacher performance.The dimension of leadership style influenced the teacher’s performance were administrator, class manager, mediator, facilitator and evaluator. The contribution number of principal leadership style and the emotional intelligence toward the performance of the teacher.